Prevalence and Risk Factors of Hypertension and Diabetes Mellitus among the Indonesian Elderly - Oktaviyani, Prisilia; salman, Salman; Sari, Marlynda Happy Nurmalita; Frisilia, Melisa; Munazar, Munazar; Satria, Ana; Maretalinia, Maretalinia (UI Scholars Hub, 2022)
Background: Epidemiological and demographic transitions lead to the emergence of non-communicable diseases (NCD) among the elderly. This study aimed to examine the risk factors of hypertension and diabetes mellitus (DM) among the elderly by using secondary data (Basic Health Research 2018). Methods: Secondary data from Basic Health Research (N = 88,911) were used. Cut-off values for measurement were WHO standard of 126 mg/dl for fasting and 200 mg/dl for non-fasting for DM and 140 mmHg for systole and 90 mmHg for diastole for hypertension. Univariate, bivariate, and multivariate (binary logistic regression) analyses were conducted using STATA version 15. Results: The prevalence of hypertension and DM among the elderly was about 22.30% and 5.39%, respectively. Age, sex, educational level, marital status, place of residence, and employment status were substantially associated with hypertension and were risk factors for DM. Conclusions: There is significant correlation between hypertension and DM are risk factors of one another and therefore show a relationship. Various sectors must develop appropriate programs, including community and family support, to address this situation.